Epithelial Tumors Of The Outer Nose - Wollina Uwe (Wolters Kluwer Medknow Publications, 2003)
The central part of the face is characterized by peculiarities in embryology and tissue composition. The outer nose is the most prominent part of the mid face exposed to UV- irradiation and sunlight. Tumors of the outer nose are not uncommon. There is a variety of nevi that may occur on the nose, but benign tumors and malignancies are also not uncommon. The most frequent malignant tumor of the region is basal cell carcinoma that needs micrographic control in case of surgical excision since frequent relapses can lead to an ulcus terebrans that may completely destroy the mid face. Most tumors need a diagnostic excision to diagnosis, some need radical excision.